A Study of Naturally Acquired Canine Babesiosis Caused by Single and Mixed Babesia Species in Zambia: Clinicopathological Findings and Case Management. (22nd November 2015) - Nalubamba, King Shimumbo; Mudenda, Ntombi Basimbi; Namwila, Mwaka Mwangala; Mulenga, Chilufya Susan; Bwalya, Eugene Chisela; M'kandawire, Ethel; Saasa, Ngonda; Hankanga, Careen; Oparaocha, Elizabeth; Simuunza, Martin
Abstract : A retrospective and prospective analysis of clinical records of dogs diagnosed with Babesia infections was carried out for the years 2000 to 2013 from practices in Lusaka, Zambia. Records of 363 dogs with confirmed Babesia infections were analysed using demographic factors including sex, breed, age, and clinical signs in relation to haematological findings and Babesia species. The clinical and laboratory findings observed are described as well as Babesia species identification. The study included 18 breeds and the highest proportion were mongrels (32.2%), males representing 64.5% of the population. The most common presenting problems were anorexia (65.3%) and lethargy/weakness (65.3%). The most common clinical signs were fever (87.3%), pallor (52.3%), lymphadenopathy (47.4%), and presence of ticks (44.9%). Anaemia (96.4%) and nucleated erythrocytes (42.2%) were the most common laboratory findings. A mixed infection of Babesia rossi and Babesia gibsoni was present in 59.7% of dogs, whilst 8% and 32.2% had B. rossi and B. gibsoni as a single infection, respectively. Case management mainly involved therapy with tetracyclines and imidocarb and was usually accompanied by clinical improvement. This study highlights, for the first time, the presence of B. gibsoni in natural dog populations in Zambia, where previously only B. rossi was reported.